Exploring the L2 selves of senior secondary students in English private tutoring in Hong Kong. (February 2019) - Yung, Kevin Wai-Ho
Abstract: Based on Dörnyei's L2 Motivational Self System (L2MSS), this study explored senior secondary students' multiple L2 selves when they enrolled in English private tutoring (EPT) courses. Through narrative inquiry, this paper analysed 18 Hong Kong Secondary Six (Grade 12) students' English learning experiences and their motivation for learning English and subscribing to EPT. Each participant completed a questionnaire, wrote three pieces of reflective writing and responded to six individual interviews throughout the year of study. The findings indicated that language learning converged from diverse activities to examination drilling at senior secondary school years. The learners possessed insecure actual L2 selves, revealing a discrepancy with their future L2 selves consisting of dominant ought-to L2 selves and suppressed ideal L2 selves. This study contributes to research in language learning by unveiling EPT learners' formation of L2 selves in a context of high-stakes testing. The findings contribute to the development of the L2MSS by operationalising the actual L2 self, its discrepancy with possible L2 selves, and the interrelationship between ideal and ought-to L2 selves. The study calls for further research to bridge the fields of shadow education and language learning given the significant role EPT plays in shaping learners' out-of-school L2 learning experiences.